Pemahaman Gender PNS di Lingkungan Dinas Pemberdayaan Perempuan dan Perlindungan Anak Pemerintah Daerah Kabupaten Bengkalis - Mufaro’ah Mufaro’ah; Titin Sumarni (HUMANISMA : Journal of Gender Studies, 2020)
This article is about the understanding and the implementation of civil servants’ gender understanding in the Department of Women's Empowerment and Child Protection in Bengkalis Regency Government. In addition, it also asks the public response on the implementation of program-based gender conducted by the civil servant. The data obtained through the questionnaires toward 36 respondents and did the interviews to the informants who have been chosen based on various interests. This data was analyzed by descriptive qualitative analysis. The results found that the civil servants’ understanding based on gender in Department of Women's Empowerment and Child Protection of the Bengkalis Regency Government already understands the gender well, so that the programs carried out always consider welfare based on gender equality. In addition, it contributes to the strengthening public knowledge about welfare based on gender equality.